We're Back, Live and Unplugged: Non-Digital Gameplay for Review and Fun - Shawn M Thorgersen Mr. (Middle Grades Review, 2022)
During the COVID-19 pandemic, middle grades students spent months isolated and, in many cases, learning remotely from teachers who were themselves scrambling to adapt to new technology. While addressing these experiences will require a multifaceted approach from stakeholders, teachers can help reintroduce students to their classrooms with student-centered, socially interactive, analog-based games intended to reinforce learning and boost engagement. This practitioner paper presents a context and a model for such play based on a popular public domain game that allows for team play, creativity, inculcation, and, frankly, fun while reviewing for mastery. The model affords teachers an extremely low-budget, student-crafted and student-executed game that can be adapted for a variety of disciplines. This paper will provide an example for an English class that has recently read excerpts from Homer’s The Odyssey.
Keywords: middle-school; post-pandemic; game-based learning; analog games; engagement